Special macromolecular self-cleaning waterproof coating for tunnel and preparation method of special macromolecular self-cleaning waterproof coating
Through the multi-layer composite structure, the tunnel polymer self-cleaning special waterproof coating is designed to utilize the synergy between high-performance resin and nano-scale functional fillers to solve the waterproofness, durability, self-cleaning and wear resistance of existing coatings in complex environments. The problem of insufficient performance has achieved the improvement of the overall performance of the coating and the extension of the service life.
Patent Information
- Application Number
- CN202411665929.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
Existing tunnel waterproof coatings are insufficient in complex environments such as high humidity, acid-base corrosion and ultraviolet irradiation, which leads to aging of the coating, water seepage, dirt accumulation and wear.
Special waterproof coating for tunnel polymer self-cleaning with multi-layer composite structure design, including the bottom waterproof layer, the intermediate reinforcement layer and the surface self-cleaning layer, through high-performance resins such as polyurethane resin, epoxy resin, fluorosilic resin and nano-level functions The synergistic effect of fillers improves the waterproof, wear resistance and self-cleaning properties of the coating.
It significantly improves the waterproofness, wear resistance and self-cleaning of the coating, extends the service life, reduces cleaning and maintenance costs, and maintains long-term effective protection performance in high humidity, high wear and corrosion environments.
Smart Images

Figure CN119463666A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coatings, in particular to a tunnel polymer self-cleaning special waterproof coating and a preparation method thereof. Background Art
[0002] Tunnels, subways, underground passages and other building structures are in a humid, closed, highly corrosive and dusty environment for a long time. Due to the high humidity of the internal environment, the tunnel surface is prone to leakage, condensation, dust and dirt accumulation. These factors not only affect the service life of the tunnel, but also increase the difficulty of daily maintenance and cleaning. In order to improve the protective performance of the tunnel environment, waterproof coatings are usually applied to the surface of the internal structure of the tunnel. However, the existing tunnel waterproof coating technology has the following deficiencies:
[0003] Lack of water resistance and durability
[0004] Most of the waterproof coatings widely used at present are single-layer structures, with resin materials (such as polyurethane or epoxy resin) as the base material. This type of single-layer coating can provide certain waterproof performance, but due to the high humidity, acid and alkali corrosive substances and temperature changes in the tunnel environment, single-layer waterproof coatings are prone to aging, cracking, water seepage and other problems after long-term use. This is because:
[0005] Single-layer resin-based coatings are prone to water penetration in a humid environment, causing the coating structure to loosen, thus affecting the waterproof effect.
[0006] The single-layer structure lacks sufficient weather resistance and cannot resist acid and alkali corrosion or the effects of ultraviolet radiation, resulting in poor coating durability and prone to aging problems.
[0007] For this reason, the single-layer structure of existing waterproof coatings is insufficient in protection and it is difficult to maintain long-term effective waterproofness and durability in complex tunnel environments.
[0008] Insufficient self-cleaning performance
[0009] Dust, exhaust gas and moisture in the tunnel environment are easy to adhere to the coating surface and form dirt. This dirt not only affects the appearance of the tunnel, but also increases the cleaning cost. Most existing waterproof coatings do not have self-cleaning functions. Even if some coatings have added self-cleaning ingredients, they are limited to simple surface hydrophilic design and do not achieve long-term effective self-cleaning effects. The reasons include:
[0010] Traditional waterproof coatings are mostly ordinary resins or have a small amount of hydrophilic materials added, which cannot achieve a super-hydrophobic effect.
[0011] Even if hydrophobic materials are added, it is difficult to maintain long-term self-cleaning properties due to the accumulation of dust particles, oily dirt and other easily attached substances in the tunnel.
[0012] Therefore, existing coatings cannot meet the self-cleaning requirements of tunnels, causing rapid accumulation of surface pollutants and increasing the frequency and cost of daily cleaning and maintenance.
[0013] Insufficient wear resistance and mechanical strength
[0014] The surface of the tunnel is easily subjected to friction and impact due to long-term exposure to complex environments. Existing waterproof coatings have obvious deficiencies in wear resistance and impact resistance, and it is difficult to maintain a complete coating structure for a long time in a high-friction environment. The deficiencies of existing single-layer or double-layer waterproof coatings in terms of wear resistance are mainly manifested in:
[0015] The coating has low strength and is easily damaged by friction and impact, resulting in coating failure or even large-scale peeling.
[0016] It is impossible to strike a balance between wear-resistant fillers and waterproof fillers, resulting in improved wear resistance and decreased waterproofness, or improved waterproofness and decreased wear resistance.
[0017] Therefore, existing coatings perform poorly in terms of wear resistance, especially under the friction, impact and vibration conditions of the tunnel environment. The coating is very prone to wear and fall off, making it difficult to achieve long-term and effective protection.
[0018] Therefore, the present invention proposes a tunnel polymer self-cleaning special waterproof coating and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention
[0019] In view of the deficiencies of tunnel waterproof coatings in the prior art in terms of waterproofness, self-cleaning, wear resistance and durability, the present invention provides a tunnel polymer self-cleaning special waterproof coating and a preparation method thereof. The coating solves the problems of leakage, pollution accumulation, wear and shedding that are prone to occur in waterproof coatings in tunnel environments through the synergistic effect of a multi-layer composite structure and functional fillers, and significantly improves the comprehensive protective performance and service life of the coating.
[0020] To achieve the above purpose, the present invention is implemented by the following technical scheme: a tunnel polymer self-cleaning special waterproof coating, comprising the following components and their weight percentages:
[0021] Polyurethane resin, 40-60wt%;
[0022] Epoxy resin, 30-50wt%;
[0023] Fluorosilicone resin, 60-80wt%;
[0024] Titanium dioxide nanoparticles, 1-5wt%;
[0025] Zinc oxide nanoparticles, 1-5wt%;
[0026] Aluminum tripolyphosphate, 0.5-2wt%;
[0027] Silica nanoparticles, 5-15wt%;
[0028] Alumina micron particles, 5-10wt%;
[0029] Carbon nanotubes, 1-5wt%;
[0030] Graphene nanosheets, 1-3wt%;
[0031] Toughening agent, 2-8wt%;
[0032] Curing accelerator, 0.1-1wt%;
[0033] The remaining solvents include anhydrous ethanol, ethyl acetate, butyl acetate and acetone.
[0034] Preferably, the coating comprises a three-layer structure, including a bottom waterproof layer, an intermediate reinforcement layer and a surface self-cleaning layer, wherein:
[0035] The thickness of the bottom waterproof layer is 1.0-1.2mm;
[0036] The thickness of the middle reinforcement layer is 0.8-1.0mm;
[0037] The thickness of the surface self-cleaning layer is 0.3-0.5mm.
[0038] Preferably, the components of the bottom waterproof layer include: 60wt% polyurethane resin, 2wt% titanium dioxide, 2wt% zinc oxide, 1wt% aluminum tripolyphosphate, 5wt% toughening agent, 0.5wt% curing accelerator, and 30wt% solvent.
[0039] Preferably, the components of the intermediate reinforcement layer include: 50wt% epoxy resin, 12wt% glass microspheres, 3wt% carbon nanotubes, 2wt% graphene nanosheets, 2wt% plasticizer, 0.3wt% catalyst, and 40wt% solvent.
[0040] Preferably, the components of the surface self-cleaning layer include: 70wt% fluorosilicone resin, 10wt% silica nanoparticles, 8wt% alumina microparticles, 2wt% polytetrafluoroethylene powder, 2wt% hydrocarbon wax particles, 3wt% fluorosilane coupling agent, and 10wt% solvent.
[0041] Preferably, the silicon dioxide nanoparticles are treated with a fluorosilane coupling agent in the surface self-cleaning layer, specifically comprising the following steps:
[0042] Adding silica nanoparticles into a mixed solution of a fluorosilane coupling agent and anhydrous ethanol, the ratio of the coupling agent to the ethanol being 1:20;
[0043] Stir the solution at 50°C-70°C for 60 minutes to ensure that the coupling agent is evenly attached to the surface of the silica particles;
[0044] After stirring, the treated silicon dioxide particles are filtered and dried at 50° C.-70° C. for 2 hours to obtain surface-modified silicon dioxide nanoparticles for use in order to improve the compatibility with the fluorosilicone resin matrix and the self-cleaning property.
[0045] Preferably, a method for preparing a tunnel polymer self-cleaning special waterproof coating comprises the following steps:
[0046] S1. Prepare the bottom waterproof layer: disperse titanium dioxide, zinc oxide and aluminum tripolyphosphate in anhydrous ethanol, and perform ultrasonic treatment for 30-40 minutes; add polyurethane resin to the filler solution and stir for 10-15 minutes, then add toughening agent and curing accelerator, let stand to remove bubbles, then spray evenly and cure;
[0047] S2, preparing the middle reinforcement layer: adding glass microbeads, carbon nanotubes and graphene nanosheets into butyl acetate and ultrasonically dispersing them for 30-40 minutes, adding epoxy resin into the mixture and stirring for 15-20 minutes, adding plasticizer and catalyst, and coating the mixture evenly on the bottom layer after standing and heating to cure;
[0048] S3. Prepare the surface self-cleaning layer: treat the silicon dioxide nanoparticles in a fluorosilane coupling agent and dry them, mix the fluorosilicone resin and other fillers in a solvent, spray them on the reinforcement layer after standing, and solidify them into a film.
[0049] Preferably, the bottom waterproof layer has a curing time of 24 hours and is cured naturally; the middle reinforcement layer has a curing time of 12 hours and is cured at 50°C; and the surface self-cleaning layer has a curing time of 24 hours and is cured in a 40°C environment.
[0050] Preferably, the bottom waterproof layer, the middle reinforcement layer and the surface self-cleaning layer are constructed by electrostatic spraying, rolling and electrostatic spraying, respectively, to ensure the uniformity and adhesion of the coating.
[0051] Preferably, a surface protection method for a tunnel structure comprises coating a tunnel polymer self-cleaning special waterproof coating on the tunnel surface to achieve waterproof, wear-resistant and self-cleaning functions on the tunnel surface.
[0052] The present invention provides a tunnel polymer self-cleaning special waterproof coating and a preparation method thereof. It has the following beneficial effects:
[0053] 1. The present invention adopts a three-layer composite structure design of a bottom waterproof layer, an intermediate reinforcement layer and a surface self-cleaning layer. Through the reasonable division of labor and synergy of each layer, it achieves comprehensive waterproof, wear-resistant and self-cleaning technical effects in the tunnel environment. Compared with the single-layer or double-layer coating structure in the prior art, the present invention introduces a multi-layer composite system in a breakthrough way, and optimizes the waterproof, reinforcement and self-cleaning functions respectively, overcoming the problems of the single coating structure and limited functions in the prior art, significantly extending the service life of the coating and improving various performances, so that it still exhibits excellent comprehensive protection performance in high humidity, high wear and corrosion environments.
[0054] 2. The present invention uses a polyurethane resin matrix in the bottom waterproof layer, supplemented by titanium dioxide and zinc oxide nanoparticles as fillers, which significantly enhances the UV resistance and corrosion resistance of the coating, achieving better waterproof and weather resistance. Compared with the waterproof coating with a single resin coating as the base material in the prior art, the present invention achieves structural waterproof improvement by introducing nano-scale functional fillers, solves the defect that the coating is easily aged and failed after being corroded by ultraviolet rays, moisture and acid and alkali substances in the tunnel environment, and enables the tunnel coating to maintain a long-term protective effect in harsh environments.
[0055] 3. The present invention uses fluorosilicone resin as the matrix in the surface self-cleaning layer, and treats silica nanoparticles with fluorosilane coupling agents, which work synergistically with aluminum oxide microparticles to construct a super-hydrophobic surface, achieving an excellent self-cleaning effect. Unlike ordinary waterproof coatings in the prior art that do not have a self-cleaning function, the present invention effectively reduces the surface energy of the coating by introducing super-hydrophobic technology, making it difficult for water droplets and dust to adhere to the coating, and surface dirt can be removed when it comes into contact with water. This technological innovation solves the problem in the prior art that tunnel coatings are difficult to clean after long-term use, thereby significantly reducing the cleaning and maintenance costs of the inner wall of the tunnel.
[0056] 4. The present invention uses an epoxy resin matrix in the middle reinforcement layer, supplemented by glass microbeads, carbon nanotubes and graphene nanosheets as composite fillers, which effectively improves the mechanical strength and wear resistance of the coating and achieves excellent impact resistance and wear resistance. Compared with the coating design with insufficient wear resistance and adhesion in the prior art, the present invention utilizes the reinforcement effect of the composite filler, which not only improves the overall strength of the coating, but also improves the adhesion to the tunnel substrate through the structural advantages of the filler. It solves the problem of the coating in the prior art that it is easy to peel off or wear out in the high-friction, high-impact tunnel environment, so that the coating can be stably attached to the tunnel surface for a long time, improving the construction quality and service life.
[0057] 5. The present invention adopts a layered construction process that combines electrostatic spraying and roller coating, and sets different curing temperatures and times for the bottom layer, middle layer and surface layer, respectively, to achieve the technical effect of high adhesion and uniform film formation. Compared with the problem of using a single construction method and uneven curing in the prior art, the present invention not only improves the uniformity of the coating and the thickness control accuracy, but also ensures good adhesion between different layers through layered coating and optimized curing process. This innovative solution solves the problems of interlayer peeling and insufficient curing in the existing coating system, making the coating easy and efficient to operate in tunnel construction, and the film-forming effect is long-lasting, which has the value of industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The present invention is a flow chart of the preparation method of tunnel polymer self-cleaning waterproof coating. DETAILED DESCRIPTION
[0059] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] Please see attached Figure 1 :
[0061] Embodiment 1:
[0062] Formula and process parameters:
[0063] Bottom waterproof layer:
[0064] Polyurethane resin: 55wt%
[0065] Titanium dioxide: 2wt%
[0066] Zinc oxide: 2wt%
[0067] Aluminum tripolyphosphate: 1wt%
[0068] Polysiloxane toughening agent: 5wt%
[0069] Curing accelerator: 0.5wt%
[0070] Solvent (anhydrous ethanol + ethyl acetate): 34.5wt% Middle reinforcement layer:
[0071] Epoxy resin: 50wt%
[0072] Glass beads: 12wt%
[0073] Carbon nanotubes: 3wt%
[0074] Graphene nanosheets: 2wt%
[0075] Plasticizer (dioctyl phthalate): 2wt% Catalyst: 0.3wt%
[0076] Solvent (anhydrous ethanol + butyl acetate): 30.7wt% Surface self-cleaning layer:
[0077] Fluorosilicone resin: 70wt%
[0078] Silica nanoparticles: 10wt%
[0079] Alumina micron particles: 8wt%
[0080] Polytetrafluoroethylene powder: 2wt%
[0081] Hydrocarbon wax particles: 2wt%
[0082] Fluorosilane coupling agent: 3wt%
[0083] Solvent (anhydrous ethanol + acetone): 5wt%
[0084] Preparation process steps:
[0085] Bottom waterproof layer: Add titanium dioxide, zinc oxide and aluminum tripolyphosphate to anhydrous ethanol, ultrasonically disperse for 35 minutes, stir for 15 minutes after adding polyurethane resin, add polysiloxane toughening agent and curing accelerator, let stand for 30 minutes, then spray evenly with electrostatic spray, and cure for 24 hours.
[0086] Middle reinforcement layer: glass microbeads, carbon nanotubes, and graphene nanosheets were ultrasonically treated in butyl acetate for 35 minutes, epoxy resin was added and stirred for 20 minutes, plasticizer and catalyst were added, and the mixture was rolled after standing for 30 minutes and cured at 50°C for 12 hours.
[0087] Surface self-cleaning layer: Silica particles are treated in fluorosilane coupling agent for 60 minutes and then dried. Fluorosilicone resin is mixed with other fillers, allowed to stand for 30 minutes and then electrostatically sprayed, and cured at 40°C for 24 hours.
[0088] This embodiment uses the median value of the composition and process parameters in the standard range. After testing, the coating exhibits good water resistance, wear resistance and self-cleaning properties, and the coating is stably attached to the surface of the substrate without falling off. The surface water contact angle is greater than 150°, showing significant superhydrophobicity. The coating also maintains high stability under high humidity and high friction conditions, and the cleaning frequency is significantly reduced, meeting the long-term protection needs of the tunnel.
[0089] The ingredients and process parameters of Example 1 are all within the recommended range, which meets the optimization criteria of the present invention, and thus has the best effect, showing the importance of the balance between ingredient ratio and process conditions.
[0090] Embodiment 2:
[0091] Formula and process parameters:
[0092] Bottom waterproof layer:
[0093] Polyurethane resin: 40wt%
[0094] Titanium dioxide: 1wt%
[0095] Zinc oxide: 1wt%
[0096] Aluminum tripolyphosphate: 0.5wt%
[0097] Polysiloxane toughening agent: 2wt%
[0098] Curing accelerator: 0.1wt%
[0099] Solvent: 55.4wt%
[0100] Intermediate reinforcement layer:
[0101] Epoxy resin: 30wt%
[0102] Glass beads: 8wt%
[0103] Carbon nanotubes: 1wt%
[0104] Graphene nanosheets: 1wt%
[0105] Plasticizer: 1wt%
[0106] Catalyst: 0.1wt%
[0107] Solvent: 58.8wt%
[0108] Surface self-cleaning layer:
[0109] Fluorosilicone resin: 60wt%
[0110] Silica nanoparticles: 5wt%
[0111] Alumina micron particles: 5wt%
[0112] Polytetrafluoroethylene powder: 1wt%
[0113] Hydrocarbon wax particles: 1wt%
[0114] Fluorosilane coupling agent: 2wt%
[0115] Solvent: 26wt%
[0116] Preparation process steps:
[0117] Bottom waterproof layer: ultrasonic treatment for 25 minutes, stirring for 10 minutes, standing for 20 minutes, then electrostatic spraying, and natural curing for 16 hours.
[0118] Middle reinforcement layer: ultrasonic treatment for 25 minutes, stirring for 10 minutes, standing for 20 minutes, then rolling and curing for 8 hours.
[0119] Surface self-cleaning layer: treated with silica particles for 45 minutes, then electrostatically sprayed and cured at 40°C for 16 hours.
[0120] The waterproofness, wear resistance and self-cleaning properties of the coating in this embodiment are all reduced. The water contact angle of the coating is about 135°, which does not achieve the ideal super-hydrophobic effect. The wear resistance test is fast, and some areas of the coating are lost and peeled off, indicating that the stability of the coating is adversely affected when the composition and process parameters are low.
[0121] Since the composition ratio and process parameters are lower than the recommended range, the performance of the coating is significantly reduced, especially the super hydrophobicity and wear resistance of the coating are poor, which cannot effectively cope with the high humidity and high friction working environment in the tunnel, indicating that parameters below the range will weaken the coating effect.
[0122] Embodiment 3:
[0123] Formula and process parameters:
[0124] Bottom waterproof layer:
[0125] Polyurethane resin: 60wt%
[0126] Titanium dioxide: 5wt%
[0127] Zinc oxide: 5wt%
[0128] Aluminum tripolyphosphate: 2wt%
[0129] Polysiloxane toughening agent: 8wt%
[0130] Curing accelerator: 1wt%
[0131] Solvent: 19wt%
[0132] Intermediate reinforcement layer:
[0133] Epoxy resin: 50wt%
[0134] Glass beads: 15wt%
[0135] Carbon nanotubes: 5wt%
[0136] Graphene nanosheets: 3wt%
[0137] Plasticizer: 3wt%
[0138] Catalyst: 0.5wt%
[0139] Solvent: 24wt%
[0140] Surface self-cleaning layer:
[0141] Fluorosilicone resin: 80wt%
[0142] Silica nanoparticles: 15wt%
[0143] Alumina micron particles: 10wt%
[0144] Polytetrafluoroethylene powder: 3wt%
[0145] Hydrocarbon wax particles: 3wt%
[0146] Fluorosilane coupling agent: 4wt%
[0147] Solvent: 5wt%
[0148] Preparation process steps:
[0149] Bottom waterproof layer: ultrasonic treatment for 45 minutes, stirring for 20 minutes, static for 45 minutes, then electrostatic spraying, and natural curing for 36 hours.
[0150] Middle reinforcement layer: ultrasonic treatment for 45 minutes, stirring for 30 minutes, standing for 40 minutes and then roller coating, curing at 50°C for 24 hours.
[0151] Surface self-cleaning layer: treated with silica particles for 80 minutes, then electrostatically sprayed and cured at 60°C for 36 hours.
[0152] The coating has good water resistance, wear resistance and self-cleaning properties overall, and the coating water contact angle is greater than 155°, which has an ideal superhydrophobic effect. However, some areas have local coating cracking and peeling due to the high proportion of fillers, indicating that excessive composition or parameters may affect the stability of the coating.
[0153] Although high values of composition and process parameters outside the recommended range showed strong performance in the short term, excessive fillers and long processing time led to local instability of the coating, indicating that the balance of composition and parameters is crucial.
[0154] Embodiment 4:
[0155] Formula and process parameters:
[0156] Bottom waterproof layer:
[0157] Polyurethane resin: 55wt%
[0158] Titanium dioxide: 3wt%
[0159] Zinc oxide: 3wt%
[0160] Aluminum tripolyphosphate: 1wt%
[0161] Polysiloxane toughening agent: 5wt%
[0162] Curing accelerator: 0.5wt%
[0163] Solvent: 32.5wt%
[0164] Intermediate reinforcement layer:
[0165] Epoxy resin: 50wt%
[0166] Glass beads: 15wt%
[0167] Carbon nanotubes: 3wt%
[0168] Graphene nanosheets: 2wt%
[0169] Plasticizer: 2wt%
[0170] Catalyst: 0.3wt%
[0171] Solvent: 27.7wt%
[0172] Surface self-cleaning layer:
[0173] Fluorosilicone resin: 75wt%
[0174] Silica nanoparticles: 12wt%
[0175] Alumina micron particles: 10wt%
[0176] Polytetrafluoroethylene powder: 1wt%
[0177] Hydrocarbon wax particles: 1wt%
[0178] Fluorosilane coupling agent: 3wt%
[0179] Solvent: 8wt%
[0180] Preparation process steps: Same as Example 1, standard curing time and temperature.
[0181] In the wear test, it showed extremely high anti-wear performance and could effectively resist high friction loss. The coating is uniform and has strong adhesion, which meets the high wear requirements of tunnel protection.
[0182] This optimized formula particularly strengthens the proportion of wear-resistant ingredients, so it performs outstandingly under friction and impact conditions and is suitable for use in high-friction environments.
[0183] Embodiment 5:
[0184] Formula and process parameters:
[0185] Bottom waterproof layer:
[0186] Polyurethane resin: 50wt%
[0187] Titanium dioxide: 2wt%
[0188] Zinc oxide: 2wt%
[0189] Aluminum tripolyphosphate: 1wt%
[0190] Polysiloxane toughening agent: 5wt%
[0191] Solvent: 40wt%
[0192] Intermediate reinforcement layer:
[0193] Epoxy resin: 45wt%
[0194] Glass beads: 10wt%
[0195] Graphene nanosheets: 2wt%
[0196] Plasticizer: 2wt%
[0197] Catalyst: 0.3wt%
[0198] Solvent: 40.7wt%
[0199] Surface self-cleaning layer:
[0200] Fluorosilicone resin: 78wt%
[0201] Silica nanoparticles: 15wt%
[0202] Fluorosilane coupling agent: 4wt%
[0203] Solvent: 3wt%
[0204] Preparation process steps: consistent with Example 1.
[0205] The surface superhydrophobicity and self-cleaning properties are significantly improved, with a water contact angle of approximately 160° and a dirt removal rate of 95% in the self-cleaning test.
[0206] This solution optimizes the superhydrophobic component and achieves a strong self-cleaning effect, making it suitable for use in highly polluted environments.
[0207] Comparative experiment:
[0208] Comparative experiment 1: Waterproof performance test
[0209] Purpose:
[0210] The waterproof performance of the coating of the present invention in the high humidity environment of the tunnel is verified, especially the key indicators such as water permeability and peeling rate under long-term water pressure, and its durability performance is evaluated.
[0211] Experimental groups
[0212] Control group A: Single-layer polyurethane coating, a common polyurethane resin coating on the market, with a thickness of about 1mm. This type of single-layer coating has basic waterproof function, but lacks long-lasting waterproofness in high humidity environments.
[0213] Control group B: double-layer coating (polyurethane + epoxy resin), traditional double-layer coating design, the bottom layer is polyurethane coating (thickness 0.6mm) for waterproofing, and the middle layer is epoxy resin (thickness 0.5mm) for wear resistance, with limited protective effect.
[0214] The coating of the present invention is a three-layer composite structure coating, wherein the bottom waterproof layer is made of polyurethane (thickness 1 mm), the middle reinforcing layer is epoxy resin (thickness 0.8 mm), and the surface layer is a fluorosilicone self-cleaning layer (thickness 0.3 mm), providing multiple functions of waterproofing, wear resistance and self-cleaning.
[0215] Experimental steps:
[0216] Water pressure penetration test: Under 0.5MPa water pressure conditions, the test was continued for 24 hours, 48 hours and 72 hours, and the water permeability of each group of coatings was recorded.
[0217] Water scouring test: The test simulates the rain environment by continuous water scouring for 72 hours, and records the peeling of the coating at different time points to evaluate the durability.
[0218] Experimental data:
[0219]
[0220]
[0221] Results Analysis and Summary
[0222] The experimental results show that the water permeability of the coating of the present invention under a water pressure of 0.5MPa is much lower than that of the control groups A and B. After 72 hours of water pressure testing, the water permeability of the coating of the present invention was only 5.2%, while the control groups A and B were 25.2% and 18.0%, respectively. In addition, the peeling rate of the coating of the present invention was only 5.4%, which was significantly lower than that of the control group. The three-layer composite design of the coating of the present invention allows the layers to work together: the bottom waterproof layer effectively blocks moisture, the high adhesion of the middle layer prevents water penetration, and the surface layer provides additional physical protection and anti-seepage capabilities. This multi-layer structural design is rare in the prior art, demonstrating the innovativeness and durable waterproof performance of the present invention in complex tunnel environments.
[0223] Comparative experiment 2: Self-cleaning performance test
[0224] Purpose:
[0225] The self-cleaning performance of the coating of the present invention in a polluted environment is verified, especially by comparing the adhesion and removal effects of pollution sources such as dust and oil.
[0226] Experimental groups
[0227] Control group A: ordinary polyurethane coating, a commonly used waterproof coating in the market (1mm thick), with poor surface hydrophobicity and inability to self-clean.
[0228] Control group B: hydrophilic self-cleaning coating, commercially available hydrophilic coating (1 mm thick), uses hydrophilic surface technology to form a thin film of water to carry away some dirt, but it is difficult to maintain long-term effectiveness.
[0229] The coating of the present invention is a three-layer composite structure super-hydrophobic coating, the surface self-cleaning layer adopts fluorosilicone resin and modified silicon dioxide nanoparticles, the water contact angle is greater than 150°, and it has super-hydrophobic properties.
[0230] Experimental steps:
[0231] Pollutant adhesion test: Sprinkle 10g / m2 of pollutant on the surface of each sample evenly. 2 Dust and oil, exposure for 72 hours, simulating dust accumulation and dirt adhesion in a tunnel environment.
[0232] Water flushing self-cleaning experiment: The contaminated sample is placed under water and flushed for 5 minutes, the amount of dirt remaining is measured, and the dirt removal rate is calculated.
[0233] Experimental data:
[0234]
[0235] Results analysis and summary:
[0236] The self-cleaning performance test showed that the dirt removal rate of the ordinary polyurethane coating (control group A) was only 17%, while the removal rate of the hydrophilic coating (control group B) was 48%. In contrast, the dirt removal rate of the three-layer super-hydrophobic coating of the present invention reached 94%, and almost no residue was left after flushing with clean water.
[0237] This shows that the present invention constructs a super-hydrophobic surface through fluorosilicone resin and silica nanoparticles treated with fluorosilane coupling agent, which significantly improves the self-cleaning property of the coating. This super-hydrophobic surface structure not only effectively repels dirt, but also removes dirt from the coating under the scouring of water flow, greatly reducing cleaning costs and maintenance frequency. Compared with hydrophilic self-cleaning technology, the super-hydrophobic design of the present invention has higher dirt removal efficiency and long-term self-cleaning advantages.
[0238] Comparative experiment 3: wear resistance test
[0239] Purpose:
[0240] The wear resistance and mechanical strength of the coating of the present invention are tested in a high friction environment such as a tunnel to verify its wear resistance and durability of adhesion.
[0241] Experimental groups:
[0242] Control group A: ordinary polyurethane coating (1mm thick), which is a commonly used single-layer tunnel protection coating with limited wear resistance.
[0243] Control group B: double-layer structural coating (polyurethane + epoxy resin), the traditional wear-resistant double-layer structure used in the market, the bottom layer is polyurethane (0.6mm) to provide waterproofing, and the middle layer is epoxy resin (0.5mm) for wear resistance, and the wear resistance performance is average.
[0244] The coating of the present invention is a three-layer composite structure coating, wherein the middle reinforcing layer adopts epoxy resin matrix composite glass microbeads, carbon nanotubes and graphene nanosheet fillers, and has high wear resistance and impact resistance.
[0245] Experimental steps:
[0246] Taber wear test: Each group of samples was subjected to 1000 friction cycles on a Taber abraser (CS-17 grinding wheel) to measure the wear amount.
[0247] Cross-cut adhesion test: After abrasion, the sample is subjected to a cross-cut test, the coating peeling area after the cross-cut is calculated, and the adhesion is evaluated (score 1-5, 5 is the best).
[0248] Experimental data:
[0249]
[0250] Results analysis and summary:
[0251] The wear test results show that the wear amount of the common polyurethane coating (control group A) is 55 mg, the peeling area is 32%, and the adhesion score is only 2 points. The wear amount of the double-layer structure control group B is 40 mg, the peeling area is 22%, and the adhesion score is 3 points. The wear amount of the coating of the present invention is only 15 mg, the peeling area is only 5%, and the adhesion score is 5 points.
[0252] The three-layer structure of the present invention, especially the design of the middle reinforcement layer, utilizes the composite effect of epoxy resin and high-strength filler to make the coating show excellent wear resistance. The fillers such as glass microbeads and carbon nanotubes in the middle layer not only enhance the impact resistance, but also effectively improve the wear resistance and adhesion. Compared with the prior art, the multi-layer composite design of the coating of the present invention takes into account waterproofness, wear resistance and adhesion, greatly improves the durability of the coating in the tunnel friction environment, and fully proves the creative improvement of the present invention.
[0253] Based on the above three comparative experiments, the coating of the present invention is significantly superior to the existing single-layer and double-layer coatings in terms of water resistance, self-cleaning and wear resistance, reflecting the synergistic effect of the multi-layer composite structure and the innovative design advantages. Specifically:
[0254] Improved waterproofness: Through the multi-layer structure design of the bottom waterproof layer, the middle reinforcement layer and the super-hydrophobic surface layer, the coating of the present invention exhibits stronger waterproof and anti-leakage performance under water pressure and humid environment, overcoming the problem of poor durability of existing single-layer and double-layer coatings.
[0255] Enhanced self-cleaning property: The super-hydrophobic surface layer design of the present invention enables dirt to fall off efficiently under the action of water flow, which far exceeds the effect of ordinary hydrophobic or hydrophilic self-cleaning coatings, and fully solves the problem of difficult cleaning and high maintenance frequency of the inner wall of the tunnel.
[0256] Significantly improved wear resistance: The middle reinforcement layer uses high-strength composite fillers, which makes the coating stable and durable under friction and impact conditions, solving the defects of the existing technology that is easy to be damaged and peeled off under high wear environment.
[0257] These experimental results fully demonstrate the innovation and technical advantages of the present invention in the field of tunnel protection, and provide a more ideal coating solution for high-humidity and high-wear environments such as tunnels and subways.
[0258] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A tunnel polymer self-cleaning waterproof coating, characterized in that: Contains the following ingredients and their weight percentages: Polyurethane resin, 40-60wt%; Epoxy resin, 30-50wt%; Fluorosilicone resin, 60-80wt%; Titanium dioxide nanoparticles, 1-5wt%; Zinc oxide nanoparticles, 1-5wt%; Aluminum tripolyphosphate, 0.5-2wt%; Silica nanoparticles, 5-15wt%; Alumina micron particles, 5-10wt%; Carbon nanotubes, 1-5wt%; Graphene nanosheets, 1-3wt%; Toughening agent, 2-8wt%; Curing accelerator, 0.1-1wt%; The remaining solvents include anhydrous ethanol, ethyl acetate, butyl acetate and acetone.
2. The tunnel polymer self-cleaning special waterproof coating according to claim 1 is characterized in that: The coating comprises a three-layer structure, including a bottom waterproof layer, an intermediate reinforcement layer and a surface self-cleaning layer, wherein: The thickness of the bottom waterproof layer is 1.0-1.2mm; The thickness of the middle reinforcement layer is 0.8-1.0mm; The thickness of the surface self-cleaning layer is 0.3-0.5mm.
3. A tunnel polymer self-cleaning special waterproof coating according to claim 2, characterized in that: The components of the bottom waterproof layer include: 60wt% of polyurethane resin, 2wt% of titanium dioxide, 2wt% of zinc oxide, 1wt% of aluminum tripolyphosphate, 5wt% of toughening agent, 0.5wt% of curing accelerator, and 30wt% of solvent.
4. The tunnel polymer self-cleaning special waterproof coating according to claim 2 is characterized in that: The components of the intermediate reinforcement layer include: 50 wt % of epoxy resin, 12 wt % of glass microspheres, 3 wt % of carbon nanotubes, 2 wt % of graphene nanosheets, 2 wt % of plasticizer, 0.3 wt % of catalyst, and 40 wt % of solvent.
5. The tunnel polymer self-cleaning special waterproof coating according to claim 2 is characterized in that: The components of the surface self-cleaning layer include: 70wt% fluorosilicone resin, 10wt% silicon dioxide nanoparticles, 8wt% aluminum oxide microparticles, 2wt% polytetrafluoroethylene powder, 2wt% hydrocarbon wax particles, 3wt% fluorosilane coupling agent, and 10wt% solvent.
6. The tunnel polymer self-cleaning special waterproof coating according to claim 1 is characterized in that: The silicon dioxide nanoparticles are treated with a fluorosilane coupling agent in the surface self-cleaning layer, specifically comprising the following steps: Adding silica nanoparticles into a mixed solution of a fluorosilane coupling agent and anhydrous ethanol, the ratio of the coupling agent to the ethanol being 1:20; Stir the solution at 50°C-70°C for 60 minutes to ensure that the coupling agent is evenly attached to the surface of the silica particles; After stirring, the treated silicon dioxide particles are filtered and dried at 50° C.-70° C. for 2 hours to obtain surface-modified silicon dioxide nanoparticles for use in order to improve the compatibility with the fluorosilicone resin matrix and the self-cleaning property.
7. A method for preparing the tunnel polymer self-cleaning waterproof coating according to any one of claims 1 to 6, comprising the following steps: S1. Prepare the bottom waterproof layer: disperse titanium dioxide, zinc oxide and aluminum tripolyphosphate in anhydrous ethanol, and perform ultrasonic treatment for 30-40 minutes; add polyurethane resin to the filler solution and stir for 10-15 minutes, then add toughening agent and curing accelerator, let stand to remove bubbles, then spray evenly and cure; S2, preparing the middle reinforcement layer: adding glass microbeads, carbon nanotubes and graphene nanosheets into butyl acetate and ultrasonically dispersing them for 30-40 minutes, adding epoxy resin into the mixture and stirring for 15-20 minutes, adding plasticizer and catalyst, and coating the mixture evenly on the bottom layer after standing and heating to cure; S3. Prepare the surface self-cleaning layer: treat the silicon dioxide nanoparticles in a fluorosilane coupling agent and dry them, mix the fluorosilicone resin and other fillers in a solvent, spray them on the reinforcement layer after standing, and solidify them into a film.
8. The method for preparing a tunnel polymer self-cleaning waterproof coating according to claim 7, characterized in that: The bottom waterproof layer has a curing time of 24 hours and is cured naturally; the middle reinforcement layer has a curing time of 12 hours and is cured at 50°C; the surface self-cleaning layer has a curing time of 24 hours and is cured in a 40°C environment.
9. The method for preparing a tunnel polymer self-cleaning waterproof coating according to claim 1, characterized in that: The bottom waterproof layer, the middle reinforcement layer and the surface self-cleaning layer are constructed by electrostatic spraying, rolling and electrostatic spraying respectively to ensure the uniformity and adhesion of the coating.
10. A surface protection method for a tunnel structure, comprising coating the tunnel polymer self-cleaning waterproof coating as claimed in any one of claims 1 to 6 on the tunnel surface to achieve waterproof, wear-resistant and self-cleaning functions on the tunnel surface.
Citation Information
Cited By
Macromolecule antiskid technology
CN120554936A
Full-life-cycle seepage-proofing and leakage-stopping multifunctional coating for subway tunnel and use method thereof
CN121136486A